In situ spectroscopy on intact Leptospirillum ferrooxidans reveals that reduced cytochrome 579 is an obligatory intermediate in the aerobic iron respiratory chain - Blake, Robert C.; Griff, Megan N. (Frontiers in Microbiology, 2012)
Electron transfer reactions among colored biomolecules in intact bacterial cells were monitored using an integrating cavity absorption meter that permitted the acquisition of accurate absorbance data in suspensions of cells that scatter light. The aerobic iron respiratory chain of Leptospirillum ferrooxidans was dominated by the redox status of an abundant cellular cytochrome that had an absorbance peak at 579 nanometers in the reduced state. Intracellular cytochrome 579 was reduced within the time that it took to mix a suspension of the bacteria with soluble ferrous iron at pH 1.7. Steady state turnover experiments were conducted where the initial concentrations of ferrous iron were less than or equal to that of the oxygen concentration. Under these conditions, the initial absorbance spectrum of the oxidized bacterium was always regenerated from that of the iron-reduced bacterium. The kinetics of aerobic respiration on soluble iron by intact L. ferrooxidans conformed to the Michaelis-Menten formalism, where the reduced intracellular cytochrome 579 represented the Michaelis complex whose subsequent oxidation appeared to be the rate-limiting step in the overall aerobic respiratory process. The velocity of formation of ferric iron at any time point was directly proportional to the concentration of the reduced cytochrome 579. Further, the integral over time of the concentraton of the reduced cytochrome was directly proportional to the total concentration of ferrous iron in each reaction mixture. These kinetic data obtained using whole cells were consistent with the hypothesis that reduced cytochrome 579 is an obligatory steady state intermediate in the iron respiratory chain of this bacterium. The capability of conducting visible spectroscopy in suspensions of intact cells comprises a powerful post-reductionist means to study cellular respiration in situ under physiological conditions for the organism.